How Does Ocha Attend Her Lectures? Lessons Learnt From an Adult Learner With a Cinderella Complex - Sumekto, Didik Rinan; Pranawa, Erry; Taufiqulloh, Taufiqulloh; Ghozali, Imam; Yuwono, Suhud Eko (Pedagogika, 2023)
This study investigates an undergraduate student with her Cinderella complex. Observation and videotape were undertaken from her agentive interactions and lectures as a single case study with the iterative and unstructured model analysis. The findings showed Ocha’s high motivation during attending her speaking classes, although her pronunciation, fluency, grammar, and vocabulary were still unsatisfactory. Ocha’s behaviors looked different from others regarding her lack of interactions with others, ignorance, introversion, egocentrics, dependence, and reticence.